The great lover : a novel - Dawson, Jill (HarperPerennial, 2009)
"In 1909, sixteen-year-old Nell Golightly is a housemaid at a popular tea garden near Cambridge University, and Rupert Brooke, a new tenant, is already causing a stir with his boyish good looks and habit of swimming naked in nearby Byron's Pool. Despite her good sense, Nell seems to be falling under the radical young poet's spell, even though Brooke apparently adores no one but himself. Could he ever love a housemaid? Is he, in fact, capable of love at all?" --Cover, p. 4.